1969
DOI: 10.1177/002221946900200307
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Sensory Integration in Educationally Handicapped Children

Abstract: Sixty-four neuromuscular, perceptual, and cognitive measurements made on 36 children with educational handicaps were subjected to Q-technique factor analysis. The two major patterns of deficits associated with low academic achievement were (1) auditory, language, and sequencing, and (2) postural and bilateral integration. Both of these syndromes were differentiated from syndromes of apraxia and tactile defensiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
56
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 8 publications
4
56
0
9
Order By: Relevance
“…Test results on the Sensory Integration and Praxis Tests, portions of the Sensory Processing Measure representing tactile overresponsiveness, and parent report of attention and activity level were included in the analyses. Exploratory factor analysis identified patterns similar to those found in early studies by Ayres (1965Ayres ( , 1966aAyres ( , 1966bAyres ( , 1969Ayres ( , 1972bAyres ( , 1977Ayres ( , & 1989, namely Visuodyspraxia and Somatodyspraxia, Vestibular and Proprioceptive Bilateral Integration and Sequencing, Tactile and Visual Discrimination, and Tactile Defensiveness and Attention. Findings reinforce associations between constructs of sensory integration and assist with understanding sensory integration disorders that may affect childhood occupation.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Test results on the Sensory Integration and Praxis Tests, portions of the Sensory Processing Measure representing tactile overresponsiveness, and parent report of attention and activity level were included in the analyses. Exploratory factor analysis identified patterns similar to those found in early studies by Ayres (1965Ayres ( , 1966aAyres ( , 1966bAyres ( , 1969Ayres ( , 1972bAyres ( , 1977Ayres ( , & 1989, namely Visuodyspraxia and Somatodyspraxia, Vestibular and Proprioceptive Bilateral Integration and Sequencing, Tactile and Visual Discrimination, and Tactile Defensiveness and Attention. Findings reinforce associations between constructs of sensory integration and assist with understanding sensory integration disorders that may affect childhood occupation.…”
supporting
confidence: 73%
“…Other patterns, such as those involving language functions or associations between two or more areas of sensory perception, were found in some studies (Ayres, 1969(Ayres, , 1972b(Ayres, , 1977(Ayres, , 1989.…”
Section: Review Of the Literaturementioning
confidence: 79%
See 2 more Smart Citations
“…Rhesus monkeys were used because of the large amount of available data on their behavior and development in laboratory settings (Harlow & Harlow, 1969;Suomi, 1997) A. Jean Ayres (1964), an occupational therapist and educational psychologist, coined the term "tactile defensiveness" to characterize the behavioral correlates of a pattern described as "feelings of discomfort and a desire to escape the situation when certain types of tactile stimuli are experienced" (1964, p. 8). Ayres showed that tactile defensiveness or overresponsiveness to tactile stimuli was consistently related to hyperactive and distractible behavior in children (Ayres, 1965(Ayres, , 1966(Ayres, , 1969(Ayres, , 1972. Overresponsiveness to tactile stimuli is easily recognized in children (McIntosh, Miller, Shyu, & Dunn, 1999) and there has been some success in treating it with sensory-based interventions (Ayres & Tickle, 1980;Mailloux, 2001;Miller, Wilbarger, Stackhouse, & Trunnell, 2002;.…”
mentioning
confidence: 99%